0109 Slow Wave Sleep Time and Its Oscillatory Features Show Opposite Associations with Emotional Memory Consolidation Following Stress. (27th May 2020) - Denis, D; Kim, S Y; Kark, S M; Daley, R T; Alger, S E; Kensinger, E A; Payne, J D
Abstract: Introduction: Sleep and stress can both enhance emotional memory consolidation. During slow wave sleep (SWS), oscillatory features such as slow oscillations (SO), sleep spindles (SS), and critically, their coupling, are believed to facilitate consolidation. How they relate to emotional memory consolidation is less clear, and how stress interacts with these oscillations is unknown. Methods: In this study, participants either underwent a psychosocial stressor (the Trier Social Stress Task; n = 32) or a control task (n=32). Next, they encoded 150 neutral, negative, and positive images while undergoing fMRI. Participants then spent the night in the lab with polysomnographic recording. The next day they were given a surprise recognition test. Results: There was better memory for emotional compared to neutral items in the stress group. Within this group, % of time spent in SWS positively correlated with emotional memory consolidation (r=.37, p=.039). However, SO-SS coupling during SWS was negatively correlated with emotional memory consolidation in the stress group (r=-.47, p=.007). This was driven by participants who showed a high cortisol response following the stressor (cortisol * coupling interaction p=.03) Results were similar when negative and positive items were analyzed separately. No correlations with neutral item memory were found. Conclusion: Sleep stage time and sleep oscillatory activity exert different effects on emotional memory following stress, and that SO-SS coupling does not always promote episodic memory consolidation. SO-SS coupling can impair emotional memories when encoded during periods of elevated stress, and accompanying neuromodulators such as cortisol are high. Support: National Science Foundation, Grant/Award Number: BXS-1539361